The Impact of Electronic Government Policy on Transparency and Accountability in Public Services - Wijaya, Sandita; Alfitri; Thamrin, M. Husni; Salya, Dida H. (International Journal of Science and Society, 2024)
Implementing the Electronic Government policy has become the main focus in efforts to increase transparency and accountability in public services. This policy is intended to change the way of interaction between government and society, expand access to information, and increase service efficiency. However, there are still various challenges that need to be overcome, including data security issues and gaps in technology access across various demographics. This research aims to evaluate the impact of Electronic Government policies on transparency and accountability in public services. This research uses a qualitative approach, collecting data from various relevant studies and sources for analysis. The data is processed to identify emerging themes and patterns, ensuring the validity and reliability of the conclusions produced. The research conclusion shows that e-government is significant in increasing transparency and accountability, by speeding up service processes and increasing public participation. However, challenges such as data security and uneven access are still major obstacles. Continuous evaluation and adaptation to feedback from the community are needed to improve and sharpen the implementation of this policy. Further development in e-government technology is also essential to overcome current weaknesses. An inclusive and sustainable development strategy will be key in making e-government a more effective tool for transparent and accountable government.